Effects of maternal protein supplementation and inclusion of rumen‐protected fat in the finishing diet on nutrient digestibility and expression of intestinal genes in Nellore steers. (17th July 2019) - da Cruz, Wendell F. G.; Schoonmaker, Jon P.; de Resende, Flavio D.; Siqueira, Gustavo R.; Rodrigues, Liziana M.; Zamudio, Germán D. R.; Ladeira, Marcio M.
Abstract: The study aimed to evaluate nutrient digestibility and intestine gene expression in the progeny from cows supplemented during gestation and fed diets with or without rumen‐protected fat (RPF) in the feedlot. Forty‐eight Nellore steers, averaging 340 kg, were housed in individual pens and allotted in a completely randomized design using a 2 × 2 factorial arrangement (dams nutrition × RPF). Cows' supplementation started after 124 ± 21 days of gestation. The feedlot lasted 135 days and diets had the inclusion of zero or 6% of RPF. Digestibility was evaluated by total feces collection. Steers were slaughtered using the concussion technique and samples of pancreas and small intestine were collected immediately after the slaughter to analyze α‐amylase activity, and the expression of SLC5A1, CD36, and CCK and villi morphometry. Feeding RPF increased nutrients digestibility ( p < 0.01). There was no effect of maternal nutrition on digestibility and α‐amylase activity in steers ( p > 0.05). Duodenal expression of SLC5A1, CD36, and CCK increased in the progeny from restricted cows. In conclusion, protein restriction during mid to late gestation of dams has long‐term effects on small‐intestine length and on expression of membrane transporters genes in the duodenum of the progeny. However, maternal nutrition does not affect digestibility in the feedlot.